Continuous endometrial volumetric analysis for endometrial receptivity assessment on assisted reproductive technology cycles - Renato Silva Martins; António Helio Oliani; Denise Vaz Oliani; José Martinez de Oliveira (BMC, 2020)
Abstract Background Human implantation is a complex process requiring synchrony between a healthy embryo and a functionally competent or receptive endometrium. In order to assess endometrial receptivity in Assisted Reproductive Technology (ART) cycles serial evaluation of endometrial volumetric analysis may have a predictive value on a positive outcome. Methods Serial 3D transvaginal ultrasound performed in women on ART cycle to evaluate embryo implantation predictors. Prospective case control study of 169 subjects were assessed. Endometrial pattern, thickness, volume and adjusted endometrial volume (ratio between endometrial volume and uterine volume) was performed to all subjects on a continuous process from baseline, during controlled ovarian stimulation, trigger day with human chorionic gonadotropin hormone (hCG) and at embryo transfer day. Results Demographics and ART procedures and scores, was similar between the two groups. Endometrial morphology also showed no difference between the two groups. Endometrial volume and adjusted endometrial volume was significantly higher in the positive group as soon as day 6 of ovarian controlled stimulation. Conclusions Serial 3D endometrial volume and adjusted endometrial volumes provides a predicting clinical tool enhancing elective embryo transfers in fresh ART cycle. Thus providing a non-invasive continuous technique for endometrial receptivity assessment that reflects endometrial changes during ART procedures.